Correction - Nomenclatural remarcks on Galdieria (Galdieriaceae, Cyanidiophytina, Rhodophyta) with description of three new species and a new lectotypification. - Del Guacchio, Emanuele; De Natale, Antonino; Pollio, Antonino (BORNH Bulletin of Regional Natural History, 2025)
There was an error in the original publication (Del Guacchio et al., 2023). When validating the names Galdieria daedala, G. partita and G. maxima on the basis of material strained in ACUF, the type localities cited in the protologues were incorrect, due to a clerical error in querying the ACUF database. Namely, the holotype of G. daedala Sentzova ex Pollio, De Natale & Del Guacchio (i.e., NAP0002462), was NOT isolated “from URSS, Kamtchatka, Uzon” BUT from Kunashir Island (Kuril Archipelago); the holotype of G. maxima Sentzova ex Pollio, De Natale & Del Guacchio (i.e., NAP0002463), was NOT from “URSS, Kamtchatka, Uzon” BUT from Kunashir Island as well; and the holotype of G. partita Sentzova ex Pollio, De Natale & Del Guacchio (i.e., NAP0002464) was NOT isolated “from Kunashir Island” BUT from the caldera Uzon in Kamtchatka (Russia). The correct localities fully match the information originally provided by Sentzova (1991). Fortunately, as the holotypes have been correctly and univocally indicated by barcode numbers, those errors do not compromise the validity of the names (Turland et al., 2018).